ANALISIS FAKTOR EKSTERNAL DAN INTERNAL YANG MEMPENGARUHI PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT (Studi Empiris pada KAP di Semarang) - Vida Fikratun Nisa; Surya Rahardja (Diponegoro Journal of Accounting, 2013)
This study aims to analyze time pressure, audit risk, materiality, review and quality control procedures and the auditor's professional commitments affecting the premature sign off audit procedures. This study is an empirical study with purposive sampling techniques of data collection. The population of this study are independent auditors who have worked for CPA’s on Semarang. The sample of this research are 73 auditors who have worked for CPA’s Semarang. There are six variables in this research that consist of five independent variables namely time pressure, audit risk, materiality, review and quality control procedures and the auditor's professional commitments and one dependent variable is the premature sign off audit procedures. Writer tested the quality of data that included validity test, reliability test, the hypothesis by means of logistic regression analysis test and friedman test. From the results of the data quality test which consists the validity and reliability test showed that all variables are valid and reliable, can be said that for the next items on the concepts of each of these variables fit for use as a measuring tool. We used Friedman test for the first hypothesis and the second to the sixth hypothesis using logistic regressions. Friedman test result indicated that the order of priority to the auditing procedures tend to be abandoned. Logistic regression test showed that variable of time pressure, audit risk, materiality, and the auditor's professional commitments have significant effect on premature sign off, while review and quality control procedures do not have significant effect on premature sign off.